(untitled) (FACE: Revista de la Facultad de Ciencias Económicas y Empresariales, 2022)
This article is a product of the research “Marketing plan for tourism in the village of El Encano, municipality of Pasto”, developed at Cesmag University in the year 2021. Problem: To contrast the economic and social situation of the township of El Encano with the current tourist offer. Objective: To identify the weaknesses of the economic and social situation of the town of El Encano in relation to the tourist offer. Methodology: The methodology used is based on the positivist paradigm and contains quantitative variables that allow analyzing economic and social aspects, in order to establish their relationship with the tourism sector of the region. Results: Describe economic and social aspects related to housing, public services and the management of the economic structure in the village of El Encano, which is directly related to the relationship of tourism as a market of inputs to provide this service in excellent quality conditions. Conclusion: The eco-economic and social situation of El Encano has some weak aspects in relation to the tourist offer that requires improvements in infrastructure, security and better living conditions and education of the people who are part of the tourist service. Originality: This research relates the economic and social aspects vis-à-vis the tourist offer to define improvement proposals taking into account the analysis of the results. Limitations: Due to the pandemic caused by Covid 19, obtaining information for this research was complex.